De Vlaamse schilderkunst in de XVIIe eeuw - De la Ruwière, Jeanne (Brussel : Artis, 1957)
Otto Vaenius - Pieter Paul Rubens - Antoon Van Dijck - Jacob Jordaens - Pieter Thys - Gaspar de Crayer - Frans Snijders - Jan Fyt - Paus de Vos - De fluwelen Breughel - Daniel Seghers